Synthesis and characterisation of multi-substituted hydroxyapatites - McCarthy, Benjamin P. (2018)
This thesis presents a range of novel mono and di-substituted hydroxyapatite powders, characterised by a range of techniques to ascertain their chemical composition, crystallographic composition, physical properties, and in vitro bioactivity.